Combination non-pharmacologic intervention for orthostatic hypotension in older people: a phase 2 study. (23rd December 2019) - Frith, James; Newton, Julia L
Abstract: Background: orthostatic hypotension (OH) is highly prevalent in older populations and is associated with reduced quality of life and increased mortality. Although non-pharmacologic therapies are recommended first-line, evidence for their use is lacking. Objective: determine the efficacy of combination non-pharmacologic therapy for OH in older people. Methods: a total of 111 orthostatic BP responses were evaluated in this prospective phase 2 efficacy study in 37 older people (≥60 years) with OH. Primary outcome was the proportion of participants whose systolic BP drop improved by ≥10 mmHg. Secondary outcomes include standing BP and symptoms. Comparison is made to the response rate of the most efficacious single therapy (bolus water drinking 56%). Therapeutic combinations were composed of interventions with known efficacy and tolerability: Therapy A- Bolus water drinking + physical counter-manoeuvres (PCM); Therapy B- Bolus water drinking + PCM + abdominal compression. Results: the response rate to therapy A was 38% (95% confidence interval – CI 24, 63), with standing systolic BP increasing by 13 mmHg (95% CI 4, 22). Therapy B was efficacious in 46% (95% CI 31, 62), increasing standing systolic BP by 20 mmHg (95% CI 12, 29). Neither therapy had a significant effect on symptoms. There were no adverse events. Conclusions: in comparison to single therapy, there is little additional benefit to be gained from combination non-pharmacologic therapy. Focussing on single, efficacious therapies, such as bolus water drinking or PCM, should become standard first-line therapy.